Peran Literasi Digital Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI - Sari, Wulan; Farida, Khusna (Prodi Pendidikan Keagamaan Islam, 2024)
At a time when the world has experienced very rapid technological progress, this is marked by the digital era entering various aspects of life. This progress makes technology easily accessible to the whole world and makes digital technology more easily available to all levels of humanity. Both in the world of politics, and business, as well as in the world of education. This research aims to determine the role of digital literacy in improving student learning outcomes in PAI subjects in class 5 of SD Syafana Islamic School Tangerang and to find out the supporting and inhibiting factors for digital-based PAI learning. This research uses descriptive qualitative research. The main data sources for this research are the school principal, PAI teachers, and class 5 students at Syafana Islamic School Primary Tangerang. Data collection techniques through interview, observation and documentation techniques. Meanwhile, technical data analysis uses Milles and Huberman analysis techniques, namely data reduction, data presentation and conclusions. The results of this research show that the role of digital literacy on student learning outcomes in PAI subjects in class 5 of Syafana Islamic School Primary Tangerang is very good. This is proven by the learning results of all class students in PAI subjects reaching the Minimum Achievement Criteria (KKM) limit. Skills in applying various digital media as a tool in delivering material, making learning more effective, innovative and creative. The supporting factors are the support and facilities provided by the school and the inhibiting factors are the limitations of students at school in utilizing digital technology.